SECTOR: Source-selective and Emission-adjusted Greenhouse Gas Calculator for Cropland - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
The SECTOR tool has been officially launched and tested with data from Vietnam and used the tool to conduct the GHG calculations for the Thai Rice NAMA tool. A scientific article as well as a tutorial and the tool itself are openly accessible.